Investigating transcranial direct current stimulation and its therapeutic potential - Dyke, Katherine (2017)
Transcranial direct current stimulation (tDCS) is a popular non-invasive brain stimulation technique, which has the potential to modulate cortical excitability. The effects of tDCS are known to outlast the stimulation period, and in some cases, repeated applications have been found to produce long lasting clinically relevant effects. The primary aim of this thesis was to explore the reliability and therapeutic potential of this technique. In Chapters 3 and 4 transcranial magnetic stimulation (TMS) was used to measure tDCS effects. These experiments revealed substantial variability regarding the way in which healthy adults responded to stimulation. Notably, there were differences between participants regarding the direction and magnitude of change in cortical excitability. Furthermore, even when group level effects were found reliably, there was substantial intra-subject variability across repeated testing sessions. Subsequent experiments in Chapters 5 and 6, explored the biological and behavioural effects of tDCS in individuals with Gille de la Tourette’s syndrome (GTS). GTS is a neurodevelopmental disorder characterised by motor and phonic tics which have been linked to hyper excitability within motor-cortical regions. Therefore, these experiments aimed to reduce cortical excitability of targeted regions in the hope that this would impact on tics. Disappointingly, no such effects were found immediately after a single session of tDCS (Chapter 5). Consequently, it was hypothesised that repeated applications may be necessary for significant reductions in tics to occur. This was investigated in Chapter 6 using an in-depth case study. The results were encouraging, in particular there was a substantial drop in tics following 10 days of tDCS at 1.5mA intensity. The stimulation was well tolerated and the treatment regimens were closely adhered to, despite tDCS being delivered in the participants own home with remote supervision. A weaker stimulation intensity was not as effective. The findings of Chapters 3-6 highlight that the optimal stimulation parameters may vary from person to person, and that exploration of individual data is critical in therapeutic contexts. The results also suggest that tDCS may be helpful as a treatment for GTS and furthermore highlight the feasibility of home use stimulation.